A step‐wise approach to define binding mechanisms of surrogate viral particles to multi‐modal anion exchange resin in a single solute system. Issue 7 (6th March 2017) - Brown, Matthew R.; Johnson, Sarah A.; Brorson, Kurt A.; Lute, Scott C.; Roush, David J.
ABSTRACT: Multi‐modal anion exchange resins combine properties of both anion exchange and hydrophobic interaction chromatography for commercial protein polishing and may provide some viral clearance as well. From a regulatory viral clearance claim standpoint, it is unclear if multi‐modal resins are truly orthogonal to either single‐mode anion exchange or hydrophobic interaction columns. To answer this, a strategy of solute surface assays and High Throughput Screening of resin in concert with a scale‐down model of large scale chromatography purification was employed to determine the predominant binding mechanisms of a panel of bacteriophage (i.e., PR772, PP7, and ϕX174) to multi‐modal and single mode resins under various buffer conditions. The buffer conditions were restricted to buffer environments suggested by the manufacturer for the multi‐modal resin. Each phage was examined for estimated net charge expression and relative hydrophobicity using chromatographic based methods. Overall, PP7 and PR772 bound to the multimodal resin via both anionic and hydrophobic moieties, while ϕX174 bound predominantly by the anionic moiety. Biotechnol. Bioeng. 2017;114: 1487–1494. © 2017 Wiley Periodicals, Inc. Abstract : A step‐wise approach was taken by the authors to define how viral particles adsorb to a surface of a multi‐modal anion exchange resin using model viruses (i.e. bacteriophage). This approach was highlighted by first defining the bacteriophages' hydrophobic and charged surface characteristics, then testing their affinity across various buffer conditions to single mode and multi‐modal resins in a high throughput batch screening. Finally the mechanisms were validated in a scaled down column.